Oral and maxillofacial medicine : the basis of diagnosis and treatment - Scully, Crispian (Churchill livingstone/Elsevier, 2013)
The new edition of this highly successful volume continues to offer readers with a systemized and objective approach to the practice of oral and maxillofacial medicine. Winner of the Royal Society of Medicine and Society of Authors Book Award in the category of 'New Authored Book' (2004), and Highly Commended in the British Medical Association Book Awards (2009), this volume is ideal for senior dental students, dental practitioners and for trainees and practitioners in oral medicine, surery, and pathology in particular. Allows the reader to adopt a systematic approach to history taking Explains how to examine patients and their oral lesions systematically to start formulating differential diagnoses Identifies which sites may be affected by the presenting condition and what to look for at the sites Explains when clinical investigations are indicated, which are appropriate, and how to perform them Shows the reader how to interpret the findings of routine clinical investigations and understand the potential implications for the patient Identifies relevant follow-up questions that may further clarify the findings of the clinical examination and refocus the history Explains how to recognise the scope of oral and maxillofacial diseases and the importance of their medical management in addition to the traditional dental focus of the discipline Shows the reader how to identify lesions and understand their potential implications for the patient Explains how to advise the patient about the aetiology of oral lesions and their predisposing factors Identifies a range of therapeutic options for the patient and emphasises the need for regular review and re-appraisal of the condition Provides an understanding of how treatment may impact, positively or negatively, upon the condition Identifies the need to refer for advice, investigations or treatment by dental, medical or surgical specialists Shows the reader how to recognise the importance of close liaison with colleagues in other disciplines, particular imaging, medicine, pathology and surgery.